Negative effects of climate warming on red-listed boreal peatland plant species can be mitigated through restoration - Christiani, Priscillia; Isoaho, Aleksi; Elo, Merja; Päkkilä, Lassi; Marttila, Hannu; Aalto, Juha; Hjort, Jan; Tolvanen, Anne; Rana, Parvez; Räsänen, Aleksi (Elsevier, 2025)
Peatlands are crucial ecosystems for biodiversity conservation and carbon storage but are largely degraded due to human impact. Climate change poses an additional threat to peatland biodiversity, affecting, for example, red-listed species. We investigate how the projected climate change and peatland restoration may jointly influence the habitat availability of red-listed peatland plant species in Finland. We use maximum entropy model to predict future changes in species distributions under different climate scenarios (representative concentration pathways [RCP] 2.6, 4.5, and 8.5) and potential restoration levels (0 %, 30 %, 50 %, and 100 % of drained peatlands) for 2040–2069 and 2070–2099. Our results show that the proportion of undrained peatland area, mean January temperature, and mean growing degree days are the main variables affecting habitat suitability for red-listed species. Furthermore, our results indicate that restoration can hypothetically expand potential suitable habitats, reduce habitat loss, moderate northward shifts, and preserve species richness. As climate warms, south and middle boreal species are projected to experience habitat expansion, while northern boreal species face more pronounced habitat loss, particularly under RCP8.5. Suitable habitat tends to shift northward for all species groups, with species richness being highest in the northern boreal zone. However, under RCP8.5 by 2070–2099, even extensive restoration cannot prevent habitat loss, northward movement, or species richness decline, particularly in the northern regions. Our findings highlight the need for immediate protection of current suitable habitats for red-listed peatland plant species and large-scale peatland restoration to ensure future suitable habitats for the red-listed species.
Keywords: restoration; climate change; peatland; habitat suitability models; red-listed species